PENGARUH DIGITAL MARKETING, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA WARUNG SERAYU DENPASAR - I Gusti Ayu Dhita Puspita Dewi; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Purchasing decision making is a process consisting of several stages, namely problem recognition, information search, alternative evaluation, purchase decisions, and post-purchase behavior. There are several factors that influence purchasing decisions, including digital marketing, product quality and service quality. This study aims to determine the effect of digital marketing, product quality and service quality on purchasing decisions at Warung Serayu Denpasar. The population used in this study is all consumers who had made purchases of Warung Serayu products. The number of samples in this study were 100 respondents who were determined using purposive sampling method with the Lemeshow formula. The analysis technique used in this research is Multiple Linear Regression Analysis, Coefficient of Determination (R2), t test. The results of the study show that Digital marketing has a positive and significant effect on purchasing decisions at Warung Serayu. Product quality has a positive and significant effect on purchasing decisions at Warung Serayu. Service quality has a positive and significant effect on purchasing decisions at Warung Serayu.